Rome’s other coinage. Contemporary counterfeit denarii - Inés Duro Cuesta; Ana Vico Belmonte; Labrador Ballestero, Patricia (Documenta & Instrumenta - Documenta et Instrumenta, 2026)
Counterfeiting has been an intrinsic feature of ancient economic systems, and the Roman denarius offers one of the most illustrative cases of this phenomenon. Once the denarius became firmly established as the principal silver coin of the Roman Republic and, subsequently, of the Empire, its imitation and fraudulent reproduction persisted as a recurrent historical practice. This study examines counterfeit Roman denarii produced in antiquity as a structural element of the Roman monetary system, considering both their economic implications and their significance as material culture. The article explores the technical, typological, and contextual traits of plated denarii (subaerati) and analyses the historical circumstances that encouraged their manufacture and circulation. Through a combined historiographical and numismatic approach, it draws a clear distinction between ancient counterfeits that formed part of the original monetary circulation and modern forgeries, emphasizing the historical value of the former as direct evidence of the economic, political, and administrative pressures that shaped the Roman world. It also reflects on the current assessment of these pieces within numismatic collecting and their gradual reappraisal as historical documents rather than mere examples of monetary fraud. From this perspective, counterfeit denarii produced in antiquity constitute a key source for understanding the limits of state control over coinage and the broader complexity of the Roman economic system.